2013
DOI: 10.1002/cphc.201200968
|View full text |Cite
|
Sign up to set email alerts
|

Tomographic Reconstruction of Designer Free‐Electron Wave Packets

Abstract: We review the generation and tomographic reconstruction of designer electron wave packets, that is, electron wave packets with a tailored momentum distribution in the continuum. Generation is accomplished by means of multiphoton ionization of an atomic prototype using polarization-shaped femtosecond laser pulses. Both the electronic structure of the neutral and interference of matter wave packets in the continuum contribute to the final shape. For the measurement of the resulting three-dimensional photoelectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 61 publications
0
35
0
1
Order By: Relevance
“…This was demonstrated with the creation and tomographic reconstruction of designer electron wave packets resulting from REMPI of potassium atoms with polarization-shaped laser pulses. [31,33,34] In the experiment presented here LIN, LCP and RCP light is used as well as elliptically polarized light. As mentioned in Section 2, for LIN the free-photoelectron wave packets are cylindrically symmetric with respect to the laser polarization.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was demonstrated with the creation and tomographic reconstruction of designer electron wave packets resulting from REMPI of potassium atoms with polarization-shaped laser pulses. [31,33,34] In the experiment presented here LIN, LCP and RCP light is used as well as elliptically polarized light. As mentioned in Section 2, for LIN the free-photoelectron wave packets are cylindrically symmetric with respect to the laser polarization.…”
Section: Methodsmentioning
confidence: 99%
“…Direct control of charge oscillations for molecular excitation [30] as well as the generation and detection of atomic ring currents [31] has been demonstrated. In addition, it has been shown that polarization-shaped laser pulses give access to the vectorial aspects of light-matter interaction [32] and that the momentum distribution of photoelectrons resulting from multiphoton ionization with polarization-shaped laser pulses can be crafted in a sophisticated fashion [33] and detected with the help of tomographic reconstruction methods. [34] On atoms, the combination of these techniques was recently used to perform a complete photoionization experiment.…”
Section: Introductionmentioning
confidence: 99%
“…The observable photoelectron flux, determined by the coherent square of the continuum wave function, exhibits a characteristic angular interference pattern in very close analogy with Young's double slit [1,3]. Another illustrative example is Young's double slit in the time domain, which has been demonstrated by atomic ionization via a coherent two-pulse laser sequence, resulting in an interference pattern in the photoelectron energy distribution [4,5]. In this case the temporal evolution of the interferogram responds to the relative phase of the laser pulses, which can be controlled via their temporal separation, and is ultimately transferred to the photoelectron wave function.…”
Section: Introductionmentioning
confidence: 91%
“…Für die Messung der Elektronenwirbel verwenden wir ein abbildendes Photoelektronen‐Spektrometer, bei dem die freigesetzten Elektronen aus dem Wechselwirkungsgebiet mit einer elektrostatischen Linse in Richtung eines abbildenden Detektors beschleunigt werden. Auf dem Detektorschirm erscheinen nur zweidimensionale (2D) Projektionen der dreidimensionalen (3D) Elektronenverteilung, weshalb wir kürzlich einen neuen Ansatz zur Rekonstruktion der vollständigen 3D‐Elektronenverteilung entwickelt haben . Ähnlich wie in der medizinischen Computertomographie entstehen 3D‐Abbildungen durch Messung von 2D‐Projektionen aus vielen verschiedenen Richtungen.…”
Section: Abbunclassified